(untitled) (Applied Biological Research, 2018)
The members of genus Bacillus are known to produce a wide range of antimicrobial substances, including peptide and lipopeptide antibiotics and bacteriocins that show wide antimicrobial spectra against food-spoilage microorganisms. The present study was aimed toevaluate the efficacy of bacteriocins from Bacillus megaterium against some selected spoilage fungi. B. megaterium was isolated from anise (Pimpinella anisum). The spoilage fungi were isolated from banana, strawberry, orange, lemon, apple, anion, cucumber, carrot, turnip and corn. Antifungal activity of extracted bactreriocin was determined at wide pH range (2-10), storage temperatures (-18, 4, 30 and 45°C for 15 days) and enzymes treatment (trypsin, pepsin, amylase and lipase) by agar well diffusion method against nine fungi. Aspergillus niger, Penicillium digitatum, Penicillium italicum and Fusarium oxysporum were found sensitive to bacteriocin and showed maximum zone of inhibition (12-16 mm). Partial characterization showed that the bactériocin was a glycolipoprotein, stable at 2-8 pH range, actives at all storage temperatures and was extracted in stationary phase of growth.